Respuesta :

I'll assume the 'g' at the end is a typo and shouldn't be there. Set the right side equal to zero and solve for x

x^2+5x-24 = 0

(x+8)(x-3) = 0

x+8 = 0 or x-3 = 0

x = -8 or x = 3

The zeros or roots are x = -8 or x = 3
❀Hm, I'm pretty sure you should solve for g. If so, then the first step we would need to do is add 24g to both sides:
gx+24g=x^224g+5x+24g
gx+24g=x^2+5x
❀Now you are going to factor out variable g:
g(x+24)=x^2+5x
❀Finally divide both sides by x+24:
[tex] \frac{g(x+24)}{x+24 } = \frac{x^2+5x }{x+24 } [/tex]

❀Your answer is:
[tex]g= \frac{x^2+5x }{x+24 } [/tex]

❀Good Luck❀